Das Individuelle verstehen: Anmerkungen zu Vittorio Hösles "Kritik der verstehenden Vernunft" - Stoll, Christian (Theologie und Philosophie, 2020)
The article comments on Vittorio Hösle’s book Kritik der verstehenden Vernunft: Eine Grundlegung der Geisteswissenschaften. It is a major achievement of the book to bring hermeneutical humanities and a strict conceptual philosophy closer together again. Hösle shows that a transcendental reflection on hermeneutical understanding leads to fundamental philosophical problems. It is only in connection with these problems that an adequate hermeneutics can be conceptualized. The article takes a critical stand on Hösle’s rejection of hermeneutics which do not focus on noematic understanding. Hösle’s critique of German historicism seems to be especially unbalanced. This also has consequences for Hösle’s account of religion and theology, which is discussed at the end.